PHONOLOGICAL AND MORPHOLOGICAL ERRORS IN STUDENTS’ READING ALOUD PRONUNCIATION AT STATE HEALTH POLYTECHNIC IN TASIKMALAYA - Vera Fatmawati (INFERENCE: Journal of English Language Teaching, 2018)
Abstract: The aim of the research is to investigate phonological and morphological errors in students’ reading aloud pronunciation. From the population of the nutritionist students (120 students), the 40 students were taken as sample of the research by purposive sampling technique. The data of the research were collected by recording the students’ pronunciation when they read aloud a text given by the lecturer. The method used is descriptive with content analysis technique. Based on the analysis results obtained, the most common phonological errors made by students in connection with surface structure taxonomy are substitutions in vowels (58.28%), and causes of error are intralingual errors in (47.42%). The most common morphological error made by students in connection with a surface structure taxonomy are omissions in suffixes (78.06%), and cause of error are intralingual errors in suffixes (95.90 %). Keywords: phonological error, morphological error, pronunciation, reading aloud